Iron-nickel-MOF / NF composite material suitable for oxygen evolution of electrolyzed water and preparation method of iron-nickel-MOF / NF composite material

By preparing iron-nickel-MOF/NF composite materials, the problem of low electrocatalytic activity of transition metal electrode materials is solved, and the efficiency and electrocatalytic activity of electrolytic water oxygen analysis reaction are improved.

CN119877014APending Publication Date: 2025-04-25CENT SOUTH UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411932149.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, transition metal electrode materials have low electrocatalytic activity in electrolytic oxygen evolution reaction, resulting in slow oxygen evolution reaction and affecting the efficiency of electrolytic hydrogen evolution.

Method used

Iron-nickel-MOF/NF composite material is used as electrode material, and by reacting nickel foam with precursor solution in an autoclave, an iron-nickel-MOF/NF composite material with excellent electrocatalytic properties is prepared.

Benefits of technology

The efficiency of the electrolytic oxygen evolution reaction is improved, the overpotential of the electrode is reduced, and the electrocatalytic activity is improved, making it an ideal oxygen evolution electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877014A_ABST
    Figure CN119877014A_ABST
Patent Text Reader

Abstract

The invention provides an iron-nickel-MOF / NF composite material suitable for electrolyzed water oxygen evolution and a preparation method thereof. The composite material with the best electro-catalytic performance is prepared by adjusting the iron-nickel ratio; the preparation process comprises the following steps: synthesizing a FeNi-MOF / NF material loaded on foamed nickel by adopting a simple one-step hydrothermal method, taking FeCl2. 4H2O, NiCl2. 6H2O and terephthalic acid as raw materials, adding NH4F and CO (NH2) 2, dissolving in a DMF / ethanol / water mixed solution, continuously stirring for 30 minutes, pouring the solution into a 50mL high-pressure kettle with a polytetrafluoroethylene lining, and carrying out heat preservation for 30 minutes at the temperature of 50 DEG C; putting the dried foamed nickel into the autoclave in a manner of inclining to the wall at a certain angle; the autoclave is then sealed and kept in an oven at 140 DEG C for 12 hours, and cooled to room temperature in the oven. The preparation method is simple, easy to operate and environmentally friendly. The electrode material prepared in the invention has good electro-catalytic performance and is an ideal oxygen evolution electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanocomposite materials, and in particular to an iron-nickel-MOF / NF composite material suitable for electrolyzing water and oxygen evolution and a preparation method thereof. Background Art

[0002] Electrocatalytic water splitting consists of the oxygen evolution reaction (OER) and the hydrogen evolution reaction (HER). The oxygen evolution reaction, which occurs together with hydrogen evolution in water electrolysis, involves a more complex four-electron transfer reaction, which occurs kinetically slowly and requires an efficient electrocatalyst to drive it.

[0003] Metal-organic framework materials (MOFs) have a unique periodic porous structure, which not only has rich and varied metal active centers, but also provides a large amount of highly accessible space to accommodate electrolytes, thus having great application prospects in catalysis and energy storage. Among them, precious metal catalysts are the most widely used and are also the most efficient OER catalysts. However, due to the scarcity and high cost of precious metals such as ruthenium, platinum, and iridium, their large-scale application is greatly affected. As an alternative, transition metals have great potential in OER. However, how to solve the problem of low electrocatalytic activity of transition metal electrode materials, which leads to slow oxygen evolution reaction, is an urgent part to be solved in improving the efficiency of hydrogen evolution by water electrolysis. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides an iron-nickel-MOF / NF composite material suitable for electrolysis of water for oxygen evolution and a preparation method thereof.

[0005] In order to achieve the above object, the technical solution of the present invention is as follows:

[0006] A method for preparing an iron-nickel-MOF / NF composite material suitable for electrolyzing water and oxygen evolution comprises the following steps:

[0007] (1) dispersing an iron source, a nickel source, an ammonium source, and an organic ligand in a solvent A to prepare a precursor solution;

[0008] (2) placing the obtained precursor solution in an autoclave, and placing the nickel foam in the autoclave at an inclined angle to the wall, so that the nickel foam reacts with the precursor solution at a set temperature. After the reaction is completed, the nickel foam is cooled to room temperature, taken out, washed, and dried to obtain an iron-nickel-MOF / NF composite material.

[0009] Furthermore, in step 1, the iron source is FeCl2·4H2O, the nickel source is NiCl2·6H2O, the ammonium source is NH4F and CO(NH2)2, the organic ligand is terephthalic acid, and the solvent A is a mixed solution of DMF, ethanol and water.

[0010] Furthermore, in step 1, the molar ratio of FeCl2·4H2O, NiCl2·6H2O, NH4F, CO(NH2)2, and terephthalic acid is 0.5:0.8-3.6:4:7:0.5.

[0011] Furthermore, in step 1, the molar ratio of FeCl2·4H2O, NiCl2·6H2O, NH4F, and CO(NH2)2 is 0.5:2:4:7:0.5.

[0012] Furthermore, in step 1, the volume ratio of DMF, ethanol and water in solvent A is 14:1:1.

[0013] Furthermore, before being placed in the autoclave, the nickel foam in step 2 is first placed in hydrochloric acid for ultrasonic cleaning, and then placed in an ethanol solution and deionized water for ultrasonic cleaning respectively.

[0014] Furthermore, in step 2, the set temperature of the autoclave is 140° C. and the reaction time is 12 h.

[0015] On the other hand, the present invention provides an iron-nickel-MOF / NF composite material suitable for electrolysis of water and oxygen evolution obtained according to the above preparation method.

[0016] In another aspect, the present invention provides an application of the product obtained according to the above preparation method in preparing an electrode.

[0017] The present invention has the following beneficial effects:

[0018] 1. The reaction device is simple, the preparation method is controllable, easy to operate and environmentally friendly;

[0019] 2. The raw materials involved are from a wide range of sources and have low costs;

[0020] 3. The prepared iron-nickel-MOF / NF composite material has good electrocatalytic performance due to its reasonably distributed iron-nickel ratio, and can be used as an ideal oxygen evolution electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Graphs showing the LSV polarization curves of the iron-nickel-MOF / NF composite materials at different iron-nickel ratios in Examples 1 to 5 of the present invention;

[0022] Figure 2 1 is an overpotential diagram of the iron-nickel-MOF / NF composite material at different iron-nickel ratios in Examples 1 to 5 of the present invention;

[0023] Figure 3 It is a Tafel plot of the iron-nickel-MOF / NF composite material at different iron-nickel ratios in Examples 1 to 5 of the present invention;

[0024] Figure 4 Electrochemical impedance spectra of the iron-nickel-MOF / NF composite materials at different iron-nickel ratios in Examples 1 to 5 of the present invention;

[0025] Figure 5 CV curves at different scanning speeds. (a) FeNi 0.8 -MOF / NF, (b)FeNi 1.2 -MOF / NF, (c)FeNi 1.6 -MOF / NF, (d)FeNi2-MOF / NF, (e)FeNi 3.6 -MOF / NF and (f) double layer capacitance diagram DETAILED DESCRIPTION

[0026] The present invention will be further described in detail below in conjunction with the examples. It should be pointed out that the examples described below are intended to facilitate the understanding of the present invention and do not have any limiting effect on the present invention.

[0027] Example 1

[0028] Step 1: Cut the nickel foam (NF) into a size of 1cm*1cm, place it in 1mol / L hydrochloric acid for ultrasonic cleaning for 15 minutes to remove the oxide layer and impurities; then place the nickel foam in ethanol solution and deionized water for ultrasonic cleaning for ten minutes respectively, and finally vacuum dry it for use.

[0029] Step 2: Weigh 0.5 mmol FeCl2·4H2O, 0.8 mmol NiCl2·6H2O, 0.004 mol NH4F and 0.007 mol CO(NH2)2 in turn into a 50 ml beaker, add 0.5 mmol terephthalic acid dissolved in 12 ml DMF / ethanol / water (v:v:v=14:1:1) mixed solution, stir continuously for 30 minutes to obtain a precursor solution.

[0030] Step 3: Pour the precursor solution into a 50 mL polytetrafluoroethylene-lined autoclave, and place the dried nickel foam into the autoclave at a set angle tilted to the wall; then seal the autoclave and keep it in an oven at 140 °C for 12 hours, and cool it to room temperature in the oven.

[0031] Step 4: Use tweezers to pick up the cooled sample and rinse it in a slow-flowing deionized water stream for about one minute to remove the attached solution; finally, put the sample into an oven and dry it at 80°C for 12 hours to obtain FeNi 0.8 -MOF / NF composites.

[0032] The prepared FeNi 0.8- LSV polarization curve, overpotential, Tafel curve, electrochemical impedance spectroscopy, cyclic voltammetry curve of MOF / NF composite materials Figure 1-Figure 5 As shown, at 100mA·cm -2 At a current density of 0.8 The overpotential required for the MOF / NF composite material is 314 mV, while the overpotential of pure nickel foam is 100 mA cm -2 When the overpotential is 377mV, the overpotential is reduced by 63mV. 0.8 -The oxygen evolution efficiency of MOF / NF composite materials is improved compared with pure nickel foam.

[0033] Example 2

[0034] Step 1: Cut the nickel foam (NF) into a size of 1cm*1cm, place it in 1mol / L hydrochloric acid for ultrasonic cleaning for 15 minutes to remove the oxide layer and impurities; then place the nickel foam in ethanol solution and deionized water for ultrasonic cleaning for ten minutes respectively, and finally vacuum dry it for use.

[0035] Step 2: Weigh 0.5 mmol FeCl2·4H2O, 1.2 mmol NiCl2·6H2O, 0.004 mol NH4F and 0.007 mol CO(NH2)2 in turn into a 50 ml beaker, add 0.5 mmol terephthalic acid dissolved in 12 ml DMF / ethanol / water (v:v:v=14:1:1) mixed solution, stir continuously for 30 minutes to obtain a precursor solution.

[0036] Step 3: Pour the precursor solution into a 50 mL polytetrafluoroethylene-lined autoclave, and place the dried nickel foam into the autoclave at a set angle tilted to the wall; then seal the autoclave and keep it in an oven at 140 °C for 12 hours, and cool it to room temperature in the oven.

[0037] Step 4: Use tweezers to pick up the cooled sample and rinse it in a slow-flowing deionized water stream for about one minute to remove the attached solution; finally, put the sample into an oven and dry it at 80°C for 12 hours to obtain FeNi 1.2 -MOF / NF composites.

[0038] The prepared FeNi 1.2 - LSV polarization curve, overpotential, Tafel curve, electrochemical impedance spectroscopy, cyclic voltammetry curve of MOF / NF composite materials Figure 1-Figure 5 As shown, at 100mA·cm -2 At a current density of 1.2 The overpotential required for the MOF / NF composite material is 288 mV, while the overpotential of pure nickel foam is 100 mA cm-2 When the overpotential is 377mV, the overpotential is reduced by 89mV. 1.2 -The oxygen evolution efficiency of MOF / NF composite materials is improved compared with pure nickel foam.

[0039] Example 3

[0040] Step 1: Cut the nickel foam (NF) into a size of 1cm*1cm, place it in 1mol / L hydrochloric acid for ultrasonic cleaning for 15 minutes to remove the oxide layer and impurities; then place the nickel foam in ethanol solution and deionized water for ultrasonic cleaning for ten minutes respectively, and finally vacuum dry it for use.

[0041] Step 2: Weigh 0.5 mmol FeCl2·4H2O, 1.6 mmol NiCl2·6H2O, 0.004 mol NH4F and 0.007 mol CO(NH2)2 in turn into a 50 ml beaker, add 0.5 mmol terephthalic acid dissolved in 12 ml DMF / ethanol / water (v:v:v=14:1:1) mixed solution, stir continuously for 30 minutes to obtain a precursor solution.

[0042] Step 3: Pour the precursor solution into a 50 mL polytetrafluoroethylene-lined autoclave, and place the dried nickel foam into the autoclave at a set angle tilted to the wall; then seal the autoclave and keep it in an oven at 140 °C for 12 hours, and cool it to room temperature in the oven.

[0043] Step 4: Use tweezers to pick up the cooled sample and rinse it in a slow-flowing deionized water stream for about one minute to remove the attached solution; finally, put the sample into an oven and dry it at 80°C for 12 hours to obtain FeNi 1.6 -MOF / NF composites.

[0044] The prepared FeNi 1.6 - LSV polarization curve, overpotential, Tafel curve, electrochemical impedance spectroscopy, cyclic voltammetry curve of MOF / NF composite materials Figure 1-Figure 5 As shown, at 100mA·cm -2 At a current density of 1.6 The overpotential required for the MOF / NF composite material is 279 mV, while the overpotential of pure nickel foam is 100 mA cm -2 When the overpotential is 377mV, the overpotential is reduced by 98mV. 1.6 -The oxygen evolution efficiency of MOF / NF composite materials is improved compared with pure nickel foam.

[0045] Example 4

[0046] Step 1: Cut the nickel foam (NF) into a size of 1cm*1cm, place it in 1mol / L hydrochloric acid for ultrasonic cleaning for 15 minutes to remove the oxide layer and impurities; then place the nickel foam in ethanol solution and deionized water for ultrasonic cleaning for ten minutes respectively, and finally vacuum dry it for use.

[0047] Step 2: Weigh 0.5 mmol FeCl2·4H2O, 2 mmol NiCl2·6H2O, 0.004 mol NH4F and 0.007 mol CO(NH2)2 in turn into a 50 ml beaker, add 0.5 mmol terephthalic acid dissolved in 12 ml DMF / ethanol / water (v:v:v=14:1:1) mixed solution, stir continuously for 30 minutes to obtain a precursor solution.

[0048] Step 3: Pour the precursor solution into a 50 mL polytetrafluoroethylene-lined autoclave, and place the dried nickel foam into the autoclave at a set angle tilted to the wall; then seal the autoclave and keep it in an oven at 140 °C for 12 hours, and cool it to room temperature in the oven.

[0049] Step 4: Use tweezers to pick up the cooled sample and rinse it in a slowly flowing deionized water stream for about one minute to remove the attached solution; finally, place the sample in an oven and dry it at a constant temperature of 80°C for 12 hours to obtain a FeNi2-MOF / NF composite material.

[0050] The LSV polarization curve, overpotential, Tafel curve, electrochemical impedance spectroscopy and cyclic voltammetry curve of the prepared FeNi2-MOF / NF composite material are shown in Figure 2. Figure 1-Figure 5 As shown;

[0051] Figure 2 In 100mA·cm -2 At a current density of , the overpotential required for the FeNi2-MOF / NF composite material is 274 mV, which is 103 mV lower than that of pure nickel foam. The highest overpotential reduction is achieved in Examples 1 to 5 of the present invention, indicating that the oxygen evolution efficiency is significantly improved, the electrocatalytic activity is high, and the reaction overpotential can be effectively reduced, thereby improving the electrochemical performance of the reaction.

[0052] exist Figure 3 In the Tafel curve, the Tafel slope of FeNi2-MOF / NF composite material is 22.5mV dec -1 , has the lowest Tafel slope among Examples 1 to 5 of the present invention, proving that the reaction rate on the electrode surface is fast, that is, the electrode has better electrocatalytic performance;

[0053] exist Figure 4In the electrochemical impedance spectrum of the FeNi2-MOF / NF composite material, the semicircle line in the spectrum has the smallest radius compared with other embodiments of the present invention, which means that its impedance value is small, the charge transfer is fast, the electrode surface reaction rate is fast, and the oxygen evolution effect is significantly improved;

[0054] Figure 5 Figures (a)-(e) are the CV curves of the electrodes at different iron-nickel ratios in Examples 1-5 obtained at different scanning speeds, and Figure (f) is the double-layer capacitance of the electrodes at different iron-nickel ratios obtained by linear fitting in (a)-(e). It can be seen that when the iron-nickel ratio increases, the double-layer capacitance of the electrodes is 3.83 mF / cm 2 、25.1mF / cm 2 , 11.89mF / cm 2 、98.96mF / cm 2 、8.94mF / cm 2 , it can be calculated that the active surface areas of the electrodes in Examples 1 to 5 are 1.915 cm 2 / cm 2 、12.55cm 2 / cm 2 、5.945cm 2 / cm 2 、49.48cm 2 / cm 2 and 4.47cm 2 / cm 2 It can be seen that in Example 4, when the iron-nickel ratio is 2, the electrode active surface area is the largest.

[0055] Example 5

[0056] Step 1: Cut the nickel foam (NF) into a size of 1cm*1cm, place it in 1mol / L hydrochloric acid for ultrasonic cleaning for 15 minutes to remove the oxide layer and impurities; then place the nickel foam in ethanol solution and deionized water for ultrasonic cleaning for ten minutes respectively, and finally vacuum dry it for use.

[0057] Step 2: Weigh 0.5 mmol FeCl2·4H2O, 3.6 mmol NiCl2·6H2O, 0.004 mol NH4F and 0.007 mol CO(NH2)2 in turn into a 50 ml beaker, add 0.5 mmol terephthalic acid dissolved in 12 ml DMF / ethanol / water (v:v:v=14:1:1) mixed solution, stir continuously for 30 minutes to obtain a precursor solution.

[0058] Step 3: Pour the precursor solution into a 50 mL polytetrafluoroethylene-lined autoclave, and place the dried nickel foam into the autoclave at a set angle tilted to the wall; then seal the autoclave and keep it in an oven at 140 °C for 12 hours, and cool it to room temperature in the oven.

[0059] Step 4: Use tweezers to pick up the cooled sample and rinse it in a slow-flowing deionized water stream for about one minute to remove the attached solution; finally, put the sample into an oven and dry it at 80°C for 12 hours to obtain FeNi 3.6 -MOF / NF composites.

[0060] The prepared FeNi 3.6 - LSV polarization curve, overpotential, Tafel curve, electrochemical impedance spectroscopy, cyclic voltammetry curve of MOF / NF composite materials Figure 1-Figure 5 As shown, at 10 mA cm -2 At a current density of 3.6 The overpotential required for the MOF / NF composite material is 288 mV, while the overpotential of pure nickel foam is 100 mA cm -2 When the overpotential is 377mV, the overpotential is reduced by 89mV. 3.6 -MOF / NF composite material has improved oxygen evolution efficiency compared with pure nickel foam; and in the cyclic voltammetry curve, the iron-nickel ratio of 3.6 in this embodiment is compared with the iron-nickel ratio of 2 in Example 4. The excessive Ni leads to a relatively low Fe content, resulting in a reduction in the effective active points on the surface area. The calculated electrode active surface area is 4.47 cm 2 / cm 2 , which is smaller than 49.48 cm in Example 4 2 / cm 2 .

[0061] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.

Claims

1. A method for preparing an iron-nickel-MOF / NF composite material suitable for electrolysis of water for oxygen evolution, characterized in that: The following steps are involved: (1) dispersing an iron source, a nickel source, an ammonium source, and an organic ligand in a solvent A to prepare a precursor solution; (2) placing the obtained precursor solution in an autoclave, and placing the nickel foam in the autoclave at a set angle to the wall, so that the nickel foam reacts with the precursor solution at a set temperature. After the reaction is completed, the nickel foam is cooled to room temperature, taken out, washed and dried to obtain an iron-nickel-MOF / NF composite material.

2. The method for preparing the iron-nickel-MOF / NF composite material suitable for electrolysis of water and oxygen evolution according to claim 1, characterized in that: In step 1, the iron source is FeCl2·4H2O, the nickel source is NiCl2·6H2O, the ammonium source is NH4F and CO(NH2)2, the organic ligand is terephthalic acid, and the solvent A is a mixed solution of DMF, ethanol and water.

3. The method for preparing the iron-nickel-MOF / NF composite material suitable for electrolysis of water and oxygen evolution according to claim 2, characterized in that: In step 1, the molar ratio of FeCl2·4H2O, NiCl2·6H2O, NH4F, CO(NH2)2 and terephthalic acid is 0.5:0.8-3.6:4:7:0.

5.

4. The method for preparing the iron-nickel-MOF / NF composite material suitable for electrolysis of water and oxygen evolution according to claim 3, characterized in that: In step 1, the molar ratio of FeCl2·4H2O, NiCl2·6H2O, NH4F, and CO(NH2)2 is 0.5:2:4:7:0.

5.

5. The method for preparing the iron-nickel-MOF / NF composite material suitable for electrolysis of water and oxygen evolution according to claim 2, characterized in that: In step 1, the volume ratio of DMF, ethanol and water in solvent A is 14:1:

1.

6. The method for preparing the iron-nickel-MOF / NF composite material suitable for electrolysis of water and oxygen evolution according to claim 1, characterized in that: Before being placed in the autoclave, the nickel foam in step 2 is first placed in hydrochloric acid for ultrasonic cleaning, and then placed in an ethanol solution and deionized water for ultrasonic cleaning respectively.

7. The method for preparing the iron-nickel-MOF / NF composite material suitable for electrolysis of water and oxygen evolution according to claim 1, characterized in that: In step 2, the set temperature of the autoclave is 140° C. and the reaction time is 12 h.

8. An iron-nickel-MOF / NF composite material suitable for electrolysis of water and oxygen evolution obtained by the preparation method according to any one of claims 1 to 8.

9. Use of a product obtained by the preparation method according to any one of claims 1 to 8 in preparing an electrode.

Citation Information

Cited By

  • In-situ converted FeCoNi MOF nanosheet catalyst as well as preparation method and application thereof

    CN121737753A